Perancangan Interior Children’s Family Centered Healthcare di Surabaya - Christina Kawatu; Hedy Constancia Indrani; purnama esa dora tedjokoesomo (Intra, 2015)
The existence of healthcare that can provide information about health education for children is needed, where they are less familiar and less know how to maintain the health of themselves. With the health facilities, the children will receive quality health care at the same time health information that can prevent children falling ill and maintain the health of themselves. The resulting design concept of the design method is inspired by the wonder health land formation Hobbit house or Hobbiton. The facility is equipped with inpatient services for children who undergo the examination. Design method used is problem of seeking and design thinking method for process design.